Financial literacy: learn smartly and wisely family’s financial planning in Gedongboyo Untung Village, Lamongan - Elliv Hidayatul Lailiyah; Sri Yaumi; Dian Lestari; Permana Sufianto; Tina Nurfitriana; Rivky Wijanarko Saputra; Yushinta Alya Putri (Community Empowerment, 2023)
The level of financial literacy in Indonesia is still low (<50%). Financial literacy is closely related to financial planning. Financial planning is not only for those who have financial difficulties, but also for those who have excess finances so that they can be planned optimally. The purpose of this community service is to increase literacy and understanding of family financial planning, so that the community, especially PKK women in Gedongboyo Untung Village can manage their family finances well. The implementation method applied is socialization and financial literacy education counseling regarding family financial planning as well as training in making doormats from used cloth. The result of this program is an increase in literacy understanding of family financial planning and its practice. In addition, it also improves the skills of participants in utilizing used cloth in the form of goods that can be used and have sale value.